Predictive ability of bedside nasal endoscopy to diagnose invasive fungal sinusitis in a pediatric population. (December 2018) - Mulvey, Carolyn L.; Rizzi, Mark D.; Buzi, Adva
Abstract: Introduction: Invasive fungal sinusitis (IFS) is a rare but deadly clinical entity that occurs in immunocompromised patients. Diagnosis in children typically requires operative biopsies under general anesthesia, which has associated risks. Findings on bedside nasal endoscopy (BNE) can be used with history, exam, and imaging to determine the need for surgery, however, the accuracy of this tool has not been established among pediatric patients. Methods: Patients who underwent BNE for evaluation of IFS from 2008 to 2016 at the Children's Hospital of Philadelphia were identified using Current Procedural Terminology (CPT) codes. Retrospective chart analysis was performed and included underlying diagnoses, presenting signs and symptoms, imaging findings, endoscopic findings and outcomes. Results: Nineteen patients were identified who underwent evaluation for IFS using BNE during the period studied. Eight patients had exam findings that were concerning for IFS, including debris or crusting, darkened or pale mucosa, or copious, thick and/or purulent secretions. Immediate operative biopsies and debridement revealed IFS in six of eight patients. Eleven patients had exam findings deemed not concerning for IFS including mucosal edema, mucous without purulence, or normal findings. Six of eleven patients underwent operative biopsy despite negative endoscopy, and five were observed clinically. None of the 11 patients with negative bedside endoscopy developed IFS. Conclusions: All patients with IFS had concerning exam findings on endoscopy and were treated with immediate biopsies and debridement. No patient with normal or non-concerning findings on BNE progressed to have invasive fungal sinusitis. While suspicion for IFS in immunocompromised children must remain high, BNE is feasible and useful in its assessment.